2001
DOI: 10.1038/labinvest.3780324
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-Antitrypsin and a Broad Spectrum Metalloprotease Inhibitor, RS113456, Have Similar Acute Anti-Inflammatory Effects

Abstract: SUMMARY:There is increasing evidence that antiproteases are able to affect the inflammatory response. To further examine this question, we administered human ␣-1-antitrypsin (␣1AT) or a synthetic metalloprotease inhibitor (RS113456) to C57 mice followed by a single intratracheal dose of quartz, a dust that evokes a marked, lasting, polymorphonuclear leukocyte (PMN) infiltrate. At 2 hours after dust administration, both antiproteases completely suppressed silica-induced PMN influx into the lung and macrophage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 28 publications
2
113
0
1
Order By: Relevance
“…Proinflammatory responses can indirectly, but powerfully, influence the commitment of Ag-activated T cells to various protective (Treg) or cytopathic phenotypes (Th1, Th2, Th17) and proinflammatory cytokines directly create ␤ cell damage and insulin resistance. To test this hypothesis, we treated new-onset overtly diabetic mice with a short course of human AAT, an acute-phase reactant with serine proteinase inhibitor (28, 29) and antiinflammatory and antiapoptotic effects (18)(19)(20)(21)(22)29). Because serum levels of AAT rise sharply in response to inflammation (30), we speculate that the function of AAT is to limit the duration and magnitude of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory responses can indirectly, but powerfully, influence the commitment of Ag-activated T cells to various protective (Treg) or cytopathic phenotypes (Th1, Th2, Th17) and proinflammatory cytokines directly create ␤ cell damage and insulin resistance. To test this hypothesis, we treated new-onset overtly diabetic mice with a short course of human AAT, an acute-phase reactant with serine proteinase inhibitor (28, 29) and antiinflammatory and antiapoptotic effects (18)(19)(20)(21)(22)29). Because serum levels of AAT rise sharply in response to inflammation (30), we speculate that the function of AAT is to limit the duration and magnitude of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse inflammation in muscle and fat causes faulty insulin signaling and insulin resistance (16) in type 2 diabetes mellitus (13) and, as recently shown, T1DM (7,17). Hence, we have tested the hypothesis that treatment with AAT, an acutephase reactant with known antiinflammatory and antiapoptotic effects (18)(19)(20)(21) including effects on islets (21,22), is effective in NOD mice with overt new-onset T1DM. In short, we are probing the hypothesis that inflammatory mechanisms trigger T1DM.…”
mentioning
confidence: 99%
“…Transcription factor NF-kB has been reported to control MMP-12 gene expression (Churg et al, 2001). Thus, we examined the localization of NF-kB in nuclear and cytyosolic fractions from A431 cells to determine whether or not NF-kB was involved in regulating MMP-12 gene expression.…”
Section: Egf Induced Nuclear Translocation Of Nf-kb Subunits P65 and mentioning
confidence: 99%
“…20 Churg et al recently have demonstrated that human alpha-1 antitrypsin (hAAT) can suppress silicainduced PMN influx into the lung and macrophage inflammatory protein-2 (MIP-2) and monocyte chemotactic protein-1 (MCP-1) gene expression. 21 Human AAT also partially suppressed nuclear transcription factor-kB (NF-kB) translocation and increased the levels of inhibitor of NF-kB (I-kB). 21 It has also been demonstrated that adenovirus-mediated AAT gene transfer can significantly decrease neointimal formation after mechanical dilation, and reverses the local inflammation that characterizes viral controls.…”
Section: Introductionmentioning
confidence: 99%